The Searching Peace through War: The Presentation of Pakistan Govt Talks with Therik Taliban Pakistan in National Press - Shaheen, Lubna; Tarique, Muhammad (Information & Media, 2022)
After over two decades of violence, loss of thousands of civilians, displacement of tens of thousands of people, and damages to key infrastructure in Pakistan by Tehrik e Taliban Pakistan (TTP), the central government decided to talk with them in 2014. These peace talks were as vital as their failure could lead inevitably to a longer war. This study is about the coverage given by the Pakistani national press on these peace talks and the military operation followed by it. It is evaluated that how far print media played their role either in initiating peace or instigating war. With this intention, Johan Galtung’s theory of Peace Journalism was applied. Analyzing the contents of four elite national English and Urdu dailies the study concluded that the mainstream press portrayed the peace talks with a considerable difference throughout peace talks, which had undermined the government approach of bringing peace. War-oriented coverage of the operation tells that whatever would be the situation media would sensationalize it. Within the news stories, mixed expressions were seen towards both peace and war but the overall coverage remained war-oriented.